Association of rs11196288 polymorphism with the development of acute cerebrovascular event. (14th October 2021) - Chernova, A; Nikulina, S; Nikulin, D
Abstract: Purpose: To study SNP rs11196288 (A> G) with development of Acute Cerebrovascular Event in the patients with cardiovascular pathology and risk factors of its development who are representatives of the east Siberian population. Material and methods: 260 patients with Acute Cerebrovascular Event participated in a research (age [57.0; 51.0–62.0]) and 272 patients of control group (age [55.0; 51.0–62.0].). Among the patients who transferred Acute Cerebrovascular Event, 157 men and 103 women. The control group included 170 men and 102 women. Inspection of the main group included: collecting complaints, anamnesis, clinical examination, computer tomography of a brain, electrocardiography, echo, ultrasonic of arteries, daily monitoring of arterial blood pressure and cardiac rhythm, analysis of a coagulant system of blood. Patients of the main group had the following cardiovascular pathology and risk factors: arterial hypertension, supraventricular tachycardia, dislipidemiya, atherosclerosis brachiocephalic of arteries, disturbances of a system of a hemostasis. The control group is examined within the international HAPIEE project. The molecular and genetic research was conducted by PCR method in real time. Statistical processing of material was carried out with use of set of the Statistica for Windows 7.0, Excel and SPSS 22 application programs. Results: As a result of the conducted research in one of the analyzed groups and subgroups statistically significant associations of genotypes and alleles of polymorphism of rs11196288 were not revealed (A> G) with Acute Cerebrovascular Event. Conclusion: SNP rs11196288 (A> G) has no significant effect on development of Acute Cerebrovascular Event in persons of the east Siberian population regardless of the previous cardiovascular pathology and risk factors. Funding Acknowledgement: Type of funding sources: None.